(untitled) (Faridpur Medical College Journal, 2020)
Surgery in jaundiced patients is associated with a higher risk of postoperative complications compared with surgery in non jaundiced patients. These complications primarily consists of septic complications, hemorrhage, superficial surgical site infection (SSSI), wound dehiscence and renal disorders. Of them Surgical Site Infection (SSI) is found more commonly than other. This study was done to evaluate the effect of delayed primary closure on preventing wound infection than that of primary closure of wound after surgery in patients with obstructive jaundice. This randomized clinical trial was carried out at the Hepatobiliary and Pancreatic division of Department of Surgery in Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2012 to June 2013. A total of 88 patients were included in this study who underwent surgical intervention for obstructive jaundice. These patients were divided into two groups randomly; control group (n=44) who underwent primary closure of the wound and experimental group (n=44) who underwent delayed primary closure of the wound. Patients demography, clinical presentation, comorbidities, pre, per and post operative variables and outcome were compared between two groups. Mean age of the patients of experimental and control group was 47.91± 14.63 and 42.25±12.13 years respectively. Duration of jaundice was significantly higher in experimental group 4.91±2.87 months than in control group 3.10±1.62 months. Postoperative wound infection was found significantly higher in control group (43.2%) than that of experimental group (11.4%). Postoperative hospital stay was significantly longer in control group (18.77± 6.24 days) than in experimental group (13.52±3.61 days). Delayed primary closure of wound reduces wound infection significantly than primary closure of wound in patients with obstructive jaundice. Faridpur Med. Coll. J. Jan 2019;14(1): 37-40